Aggregation-induced emission characteristics and distinct fluorescent responses to external pressure stimuli based on dumbbell D-π-A-π-D cyanostyrene derivatives. Issue 50 (11th December 2020) - Zhao, Qian; He, Jianwei; Yang, Wenjun; Zhang, Haichang; Lin, Liming; Jin, Fei; Zhan, Yong
Abstract: Two dumbbell cyanostyrene derivatives PBCAN and PBTAN have been designed and prepared. Quantum chemical calculations and optical spectra confirm that two compounds are D-π-A-π-D structures. Both of them show aggregation-induced emission (AIE) characteristic, giving high emission efficiency in solid state. Interestingly, two molecules exhibit distinct fluorescent response to external pressure stimuli. Upon the treatment of grinding, PBCAN exhibits unusual hypsochromic shift of the emission wavelength of 10 nm, while PBTAN shows bathochromic shift of 18 nm. We think that the former might be due to close molecular packing in the initial state, while the latter might be derived from the transformation of π-packing mode from H -aggregate to J -aggregate. The current result is valuable for exploiting structurally similar molecules with distinct MFC characteristics. Graphical abstract: Image 1 Highlights: Two dumbbell D-π-A-π-D type cyanostyrene derivatives PBCAN and PBTAN have been synthesized. They exhibit aggregation-induced emission and distinct fluorescence response to mechanical force. The blue-shifted mechanochromism of PBCAN might be originated from close molecular packing in original state. The conversion of π-stacking from H -aggregate to J -aggregate caused red-shifted mechanochromism of PBTAN.